The Relationship Between the Application of E-Modules Based on Mangrove Forest Ecotourism on the Peace-Loving Character of Students - Asrial, Asrial; Syahrial, Syahrial; Kurniawan, Dwi Agus; Zulkhi, Muhammad Dewa (Journal of Education Technology, 2021)
Teachers still find it difficult to use technology to develop open materials for students, so that it has an impact on low student learning outcomes. The purpose of this study was to analyze the peace-loving character of students after an electronic module based on local wisdom ecotourism of The Basal Babu Mangrove Forest was applied. This type of research is quantitative with research methods using quantitative associative research. The sample in this study was 32 fourth-grade elementary school students. The sampling technique was total sampling. The techniques used to collect data are observation, interviews, and questionnaires. The data collection instrument used was a questionnaire. The data analysis technique used descriptive statistics and inferential statistics. The result in this study is that the cinta damai character owned by the students has a good category, seen from the peace-loving character after the electronic module based on local wisdom, using the correlation results obtained 0.937 and the results of a positive relationship. This shows that there is a relationship between the peace-loving character and the application of the electronics module. This research implies that the application of this electronic module helps students learn independently and can improve students' character.